Measurement of Slip, Force and Deformation Using Hybrid Tactile Sensor System for Robot Hand Gripping an Object. (31st January 2013) - Kawamura, Takuya; Inaguma, Naoto; Nejigane, Ko; Tani, Kazuo; Yamada, Hironao
A hybrid tactile sensor system is proposed for a robot hand to hold and grip an object adaptively as the sensor system measures the slip of an object, the gripping force, and the deformation of its silicon rubber sensor element. A hybrid tactile sensor system consists of a Carbon Micro-Coil (CMC) touch sensor and a force sensor. The CMC sensor element is made of silicon rubber containing CMCs several micrometres in diameter. It is considered that the sensor element constitutes an LCR circuit, and the CMC touch sensor, deformed mechanically, produces signals due to the modification of the circuit. In this study, a dome-shaped CMC sensor element similar to the shape of a human fingertip was used. This paper first examines the characteristics of the CMC sensor in terms of slip detection when the sensor system held and released an object. Next, the characteristics of the CMC element are clarified with respect to the compression force and deformation when the CMC element was compressed vertically. Finally, methods using the hybrid tactile sensor system are developed to detect the slip of an object and estimate the magnitude of deformation of the CMC element.